Influence of environmental awareness on the ecoefficiency of families in New City district, 2019 - Torres Zapata, María del Pilar (2020)
The objective of the research was Analyze the influence of environmental awareness in the families of the Ciudad Nueva district. The time horizon of the investigation corresponds to the first semester of the year 2019. Information was gathered from 366 families from the district of Ciudad Nueva. The methodology focused on the basic quantitative approach of correlational scope, being its non-experimental, transversal retrospective design. It was found with a statistical security of 99%, which is weak and positive (r=+0.253**) the influence of environmental awareness on the efficient use of water in the families of the Ciudad Nueva district. Likewise, it was found with a statistical security of 99%, which is moderate and positive (r=+0.418**) the influence of environmental awareness on the efficient use of energy in the families of the district of Ciudad Nueva. Likewise, it was found with a statistical security of 99%, which is weak and positive (r=+0.355**) the influence of environmental awareness in the efficient management of waste in the families of the Ciudad Nueva district. Finally, a weak, positive and highly significant correlation was found between the variables environmental awareness and eco-efficiency (r = + 0.386 **). These results allow us to confirm with a statistical security of 99%, that environmental awareness positively influences the eco-efficiency of families in the district of Ciudad Nueva.